THE EFFECT OF WORKING CAPITAL TURNOVER, RECEIVABLE TURNOVER, AND INVENTORY TURNOVER ON THE PROFITABILITY OF FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2018-2022 PERIOD - Firastika, Firastika; Abdul Muttalib; Abdul Salam (International Journal of Economic Research and Financial Accounting, 2024)
Objectives This research is a type of quantitative research with the aim of determining the Influence of Working Capital Turnover, Receivable Turnover, and Inventory Turnover on the Profitability of Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period. The type of data in this study is secondary data, namely data obtained indirectly, through intermediaries in the form of data on food and beverage companies listed on the Indonesia Stock Exchange (IDX). The data used in this study is the annual financial report of food and beverage companies for the period 2018-2022. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26 application regarding the Effect of Working Capital Turnover, Receivable Turnover, and Inventory Turnover on the Profitability of Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period, the author draws important conclusions, namely Working Capital Turnover has a positive and significant effect, Receivable Turnover has a negative and significant effect and Inventory Turnover has a positive and significant effect on profitability in Food And Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period.